2023
DOI: 10.3390/biomedicines11071892
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Therapy and Its Future Prospects for Ameliorating COVID-19: Clinical Applications, Efficacy, and Modality

Ishrat Perveen,
Bakhtawar Bukhari,
Mahwish Najeeb
et al.

Abstract: Molecular hydrogen is renowned as an odorless and colorless gas. The recommendations developed by China suggest that the inhalation of hydrogen molecules is currently advised in COVID-19 pneumonia treatment. The therapeutic effects of molecular hydrogens have been confirmed after numerous clinical trials and animal-model-based experiments, which have expounded that the low molecular weight of hydrogen enables it to easily diffuse and permeate through the cell membranes to produce a variety of biological impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Additionally, it is possible that a higher concentration of hydrogen gas would have elicited a more noticeable effect. Indeed, some studies use up to 66.67% inhalation of hydrogen gas such as with COVID-19 patients [26]. However, we chose 4% H 2 because clinical research has shown therapeutic effects using 2-4% H 2 [27] and H 2 gas is not flammable blow a 4.6% concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is possible that a higher concentration of hydrogen gas would have elicited a more noticeable effect. Indeed, some studies use up to 66.67% inhalation of hydrogen gas such as with COVID-19 patients [26]. However, we chose 4% H 2 because clinical research has shown therapeutic effects using 2-4% H 2 [27] and H 2 gas is not flammable blow a 4.6% concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular hydrogen therapies were also seen to be effective in remediating the dangerous consequences of COVID-19 infection. Hydrogen administration inhibited cytokine cascade and decreased inhalation resistance in patients with mild to moderate disease [23]. Although hydrogen has shown potential in the last few years, it is still too early to conclude its usefulness.…”
Section: Covid-19 and Hydrogen-rich Watermentioning
confidence: 99%
“…Many basic and clinical studies have explored the role of hydrogen in various conditions, including respiratory diseases, 27,81,[85][86][87][88] cardiovascular diseases, 89 neurological disorders, 90,91 gastrointestinal diseases, 92,93 musculoskeletal disorders, 94,95 immune system disorders, 96 98 and multiorgan damage caused by COVID-19. 88,99,100 Overall, hydrogen therapy has shown potential in treating numerous diseases.…”
Section: Basic and Preclinical Studies Of Hydrogen Therapy For Diseasesmentioning
confidence: 99%